Cell‐assisted lipotransfer: Friend or foe in fat grafting? Systematic review and meta‐analysis. (7th December 2017) - Laloze, J.; Varin, A.; Gilhodes, J.; Bertheuil, N.; Grolleau, J.L.; Brie, J.; Usseglio, J.; Sensebe, L.; Filleron, T.; Chaput, B.
Abstract: Autologous fat grafting is a common procedure for soft‐tissue reconstruction but is associated with a graft resorption rate ranging from 20% to 80%. To improve the fat graft survival rate, a new technique, called cell‐assisted lipotransfer (CAL), was developed. With CAL, fat is injected along with adipose‐derived stromal cells that are assumed to improve fat survival rate. We conducted an evidence‐based meta‐analysis to evaluate the efficacy and safety of CAL as compared with conventional autologous fat grafting (non‐CAL). The databases MEDLINE (via PubMed), Cochrane Library, EBSCO, Web of Science, and EMBASE were searched for reports of clinical trials, case series, and cohorts available from 2008 to 2016. We conducted a meta‐analysis of the efficacy of CAL with data analysis concerning fat survival rate. The incidence of complications and the need for multiple procedures were evaluated to determine the safety of CAL. We identified 25 studies (696 patients) that were included in the systematic review; 16 studies were included in the meta‐analysis to evaluate the efficacy of CAL. The fat survival rate was significantly higher with CAL than non‐CAL (64% vs. 44%, p < .0001) independent of injection site (breast and face). This benefit of CAL was significant for only injection volumes <100 ml ( p = .03). The two groups did not differ in frequency of multiple procedures after fat grafting, but the incidence of complications was greater with CAL than non‐CAL (8.4% vs. 1.5%, p = .0019). The CAL method is associated with better fat survival rate than with conventional fat grafting but only for small volumes of fat grafting (<100 ml). Nonetheless, the new technique is associated with more complications and did not reduce the number of surgical procedures needed after the first fat grafting. More prospective studies are required to draw clinical conclusions and to demonstrate the real benefit of CAL as compared with common autologous fat grafting.